Research on the Detection Countermeasures of Telecommunication Network Fraud Based on Big Data for Killing Pigs and Plates. (7th March 2022) - Li, Gang; Wen, Yong
Abstract : This paper uses big data analysis to conduct in-depth analysis and research on the investigation countermeasures of the pig-killing dish telecommunication network fraud. This paper takes the case of "piggy bank" as a perspective, starting from analyzing the concept and characteristics of "piggy bank" type network fraud, analyzing the current phenomenon of this type of network fraud crime, and analyzing the current situation of the relevant laws, to explore the judicial situation regarding this type of network fraud crime, and to explore the problems and dilemmas in the judicial determination of such network fraud crimes, the determination of evidence, the determination of principal and accessory in joint crimes, the determination of crime amount, the determination of attempt and attempt form, and the determination of related crimes. Based on the analysis of the problems, the judicial determination process of "piggyback" network fraud is improved in terms of perfecting the evidence determination process, combining the facts of the whole case to determine the joint crime, accurately characterizing the associated criminal acts, regulating the judicial determination rules of the crime amount, and strictly applying the criteria of the circumstances of attempt and completion. This paper explores the forward shift of investigation work, anticipating telecommunication network fraud crimes in advance or the middle of the matter through active investigation, taking technical countermeasures, especially early warning and dissuasion to avoid the occurrence of telecommunication network fraud crimes, and reversing the unfavorable situation of passive investigation in the past. Finally, it focuses on the strategy and innovation points of the use of network investigation methods in telecom fraud crimes and proposes the investigation method of tracing the money chain and information chain along the line and cross-complementing the two lines at the same time according to the characteristics contained in telecom fraud crimes, relying on multiple groups such as public security, hackers, and network volunteers to jointly combat in a variety of network environments.